PEMILIHAN STRATEGI ENERGI UNTUK MENDORONG PEMANFAATAN EBT DI SEKTOR TRANSPORTASI - permana, adhi d; yudiartono, yudiartono; fitriana, ira; Dewi, Ratna E. P; zuldian, prima (Jurnal Sains dan Teknologi Indonesia, 2012)
The transportation sector is the second largest final energy consumer after the industry sector. The main energy issue in the transportation sector in Indonesia is the dominant use of oil fuels. Moreover, almost 60% of total oil fuels are being subsidized. On the contrary, the development and application of New and Renwable Energy (NRE) in the transportation sector has not been very successful. This paper applies the Analytical Hirarchy Process (AHP) in conjuction with optimization of the energy system using MARKAL model to select the best strategy for increasing the role of New and Renewable Energy (NRE) in the transportation sector. Three case studies are applied to evaluate the intervention by policy as an effort to increase the role of NRE in the transportation sector.